2017
DOI: 10.1177/0883073817690094
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Serine Biosynthesis Defect Due to Phosphoglycerate Dehydrogenase Deficiency: Variability in Phenotype and Treatment Response, Novel Mutations, and Diagnostic Challenges

Abstract: Serine biosynthesis defects can present in a broad phenotypic spectrum ranging from Neu-Laxova syndrome, a lethal disease with multiple congenital anomalies at the severe end, to an infantile disease with severe psychomotor retardation and seizures as an intermediate phenotype, to a childhood disease with intellectual disability at the mild end. In this report we present 6 individuals from 3 families with infantile phosphoglycerate dehydrogenase (PGDH) deficiency who presented with psychomotor delay, growth fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Their brain MRI did not show evidence of corpus callosum atrophy and hypomyelination in the infantile form. Remarkably, three patients had been reported to lose the ability to walk independently (Benke et al, 2017). We speculated that regression could also be a feature of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their brain MRI did not show evidence of corpus callosum atrophy and hypomyelination in the infantile form. Remarkably, three patients had been reported to lose the ability to walk independently (Benke et al, 2017). We speculated that regression could also be a feature of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…PHGDH gene mutations are associated with two kinds of disease phenotypes: classical PHGDH deficiency (OMIM: 601815) and Neu–Laxova syndrome (NLS, OMIM: 256520). Since first reported by Jaeken et al (1996), a total of 43 patients with the PHGDH gene variants were identified in 23 articles (Abdelfattah et al, 2020; Acuna‐Hidalgo et al, 2014; Benke et al, 2017; Brassier et al, 2016; Cavole et al, 2020; de Koning et al, 1998; el‐Hattab et al, 2016; Glinton et al, 2018; Häusler et al, 2001; Jaeken et al, 1996; Klomp et al, 2000; Kraoua et al, 2013; Mattos et al, 2015; Méneret et al, 2012; Ni et al, 2019; Pind et al, 2002; Pineda et al, 2000; Poli et al, 2017; Shaheen et al, 2014; Tabatabaie et al, 2009, 2011; Takeichi et al, 2018; Tao & Lu, 2021). An overview of clinical characteristics in patients who were reported with clear genetic etiology of PHGDH gene mutations is summarized in Data S1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, CSF serine and glycine concentrations are not affected by meals, however, CSF amino acid analysis is not typically done in the absence of seizures. Therefore, the metabolic work up may fail to identify children with serine biosynthesis defects [27,33].…”
Section: Introductionmentioning
confidence: 99%
“…PHGDH is involved in nucleotide synthesis by supporting central one-carbon metabolism [16]. Furthermore, in the last decade, several mutations have been correlated to PHGDH deficiency [17][18][19]. Five homozygous missense mutations have been identified in several individuals with congenital microcephaly, psychomotor retardation and variable presence of seizures [17,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%